Essays on the political economy of protest voting - Cefala, Edoardo (2022)
The aim of this thesis is to study the causal effect of massive migration waves on political attitudes and voting. I show in particular how large inflows of migrants were able to shape both attitudes and elections historically and also in more recent periods. The first chapter shows that the arrival of immigrants from Eastern European countries after the European enlargement caused an increase in Euroscepticism in Great Britain. The second chapter studies instead, how an important wave of forced migration was able to shape both electoral outcomes and party strategy in 1960s France. In the third chapter, I focus my attention on a different topic: the political effect of the Labour's economic response to the financial crisis. I show that areas that are likely to have benefited from Labour's policies after the crisis, started to vote more favourably for the Labour party.